Looking for a guide to protect the environment: The development of the precautionary principle - Giovanni Immordino (Fondazione Eni Enrico Mattei (FEEM), 2000)
If the precautionary principle must become the guide of the international community for environmental protection policies, an economic interpretation of the principle is in order. The analysis of case studies and a survey of the recent decision theoretic literature show on the one hand, the difficulty of applying the principle due to the vagueness of the law and, on the other, the lack of a completely satisfactory economic modelling. More generally various theoretic and empirical results demonstrate that the precautionary principle cannot be assumed to apply a priori. The precautionary principle, proposed by international treaties as a rule of thumb to be used in situations of scientific uncertainty, could indeed be inefficient.
Keywords: H0; O13; D8; 330; Precautionary Principle; self-protection; self-insurance; comparative statics; information structure; Umweltvorsorge; Umweltschutz; Theorie